Novel pH-responsive dextrin nanogels for doxorubicin delivery to cancer cells with reduced cytotoxicity to cardiomyocytes and stem cells - Manchun, S.; Cheewatanakornkool, K.; Dass, Crispin; Sriamornsak, P. (Elsevier, 2014)
The aim of this study was to develop pH-responsive dextrin nanogels (DNGs) capable of triggered intracellular DOX release at the lower pH of cancer cells. DNGs were prepared by an emulsion cross-linking method using glyoxal as cross-linker to create an acid-labile bond. A higher molecular weight of dextrin with increasing mole ratio of dextrin to glyoxal decreased the average diameter of DNGs. DNGs showed slightly negative surface charge and pH-responsive behavior. The in vitro drug release was slow at pH 7.4 and increased with decreasing pH (pH 5 > 6.8). The cytotoxicity of DOX-loaded DNGs in mesenchymal stem cells and cardiomyocytes was lower than that of free DOX. Moreover, DOX-loaded DNGs were efficiently internalized by tumor cells with rapid release of DOX into the nucleus. Thus, DOX-loaded DNGs were successful for intracellular targeted anti-tumor drug delivery and reducing side-effects to non-tumor cells such as cardiomyocytes and stem cells.